A COMPARATIVE STUDY BETWEEN THE ABILITY OF THE SECOND YEAR MALE AND FEMALE STUDENTS OF SMP IT AZIZIYYAH PEKANBARU ON COMPREHENDING DESCRIPTIVE TEXT - Ranti Hardita; Jismulatif Jismulatif; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aimed to find out the ability level of male and female students and the significant difference between the ability of the second year male and female students of SMP IT Aziziyyah Pekanbaru on comprehending descriptive texts. The research was conducted from March 18, 2019 up to April 10, 2019. The population of this research was the second year students of SMP IT Aziziyyah Pekanbaru with the total number of 88 students (52 males and 36 females). A purposive sampling technique was used to determine the sample of the research. The total sample was 72 students that consisted of 36 male students and 36 female students. To collect the data in this research multiple choice tests were used. Descriptive text was used to know the students' ability on reading comprehension. The result of the research showed that the ability of the second year male and female students of SMP IT Aziziyyah Pekanbaru on comprehending descriptive texts is in good level and there is no significant difference on comprehending descriptive texts in term of their genders. It means that Null hypothesis (H0) is accepted and Alternative hypothesis (H1) is rejected.Key Words: Comparative, Gender, Reading, Descriptive Text